The Time History of a Specific Area in Yogyakarta with a Subduction Earthquake Source Based on the 2002 Earthquake Map - Wisnu Erlangga; Mochamad Teguh; Lalu Makrup; Jafar; Maharani Dagi Saputri (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2023)
Indonesia is a country that is very prone to earthquake disasters. Earthquakes cause damage especially to buildings. In building planning, the usual earthquake load is the earthquake load from the spectral response. The use of earthquake loads from time history is very rarely used because of the difficulty of finding accurate data for an area. In this study, Alana Hotel and Apartment were chosen as research objects to find artificial time history. All earthquake data affecting Yogyakarta region were collected from several sources. Seismic hazard analysis in this study uses the PSHA (Probabilistic Seismic Hazard Analysis) method by calculating the main earthquake only. The selection of attenuation functions is based on the similarity of geological and tectonic conditions in Indonesia. These attenuation functions produce a seismic hazard curve and a uniform hazard spectrum response. The selection of time history data for bedrock is based on the results of the deaggregation process in the form of dominant magnitude and dominant distance from the subduction earthquake source. It is necessary to adjust the spectrum response in the time history data to fit the research location. Furthermore, earthquake waves from the bedrock are propagated to the surface. The results show that the peak time history acceleration value after surface propagation increased by 1.51 times than the time history in bedrock.